Gamma attenuation characteristics of CdTe-Doped polyester composites. (January 2021) - Akman, F.; Ogul, H.; Kaçal, M.R.; Polat, H.; Dilsiz, K.; Agar, O.
Abstract: Polyester is strong and durable material and tends to retain its shape, thus polyester composites have become highly preferred option in high-tech applications. This motivates the usage of polyester composites in the production of radiation shielding materials as well. In present study, gamma ray shielding properties of polyester composite reinforced with different proportions of Cadmium Telluride (5%, 10%, 15% and 20%) have been investigated theoretically and experimentally. The experiments were performed with the use of HPGe detector in a wide range of photon energies varying from 59.5 to 1408.0 keV while XCOM computer program was computed in the same photon energy range to obtain theoretical results and to verify the experimental outcomes. Remarkable radiation protection efficiency was obtained with additive material of Cadmium Telluride, and the radiation protection efficiency was found to be increased with the increase of additive material amount. Negligible discrepancies between experimental and theoretical results were also observed. Graphical abstract: Image 1 Highlights: Polyester composites reinforced with CdTe were produced for the first time. The gamma-ray attenuation capacities of the composites were investigated. Experimental and theoretical studies were carried out in a wide energy range. Remarkable radiation protection efficiency was obtained with additive of CdTe. CdTe(20%) coded sample has better gamma-ray attenuation than other samples.